PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW BERBANTUAN WEB TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPS KELAS VIII DI SMPN 2 LUBUK SIKAPING - Hanifa Zahara; Abna Hidayati; Rayendra; Mutiara Felicita Amsal (STKIP Subang, 2026)
The low learning outcomes of students in social studies are influenced by one-way learning, low student participation, and the ineffectiveness of the learning model. This study aims to determine the effect of the web-assisted jigsaw cooperative learning model on student learning outcomes in social studies for class VIII at SMPN 2 Lubuk Sikaping. This study uses a quantitative approach with a quasi-experimental method with a nonequivalent control group design. The research sample consisted of two classes, namely the experimental class and the control class, each consisting of 25 students. Data collection techniques used tests in the form of pretests and posttests. Data were analyzed using normality tests, homogeneity tests, and t-tests. The results showed that the average value obtained from the learning outcomes of students in the experimental class who applied the web-assisted jigsaw model was 75, while the control class who applied conventional learning obtained a learning outcome value of 66. Based on the t-test, the t-test was obtained 2.069 and t-table 1.677 at a significance level of α = 0.05. Therefore, if the calculated t value is 2.069 > t table 1.677, it can be interpreted that H1 is accepted and H0 is rejected. Therefore, it can be concluded that there is a significant effect of the implementation of the web-assisted jigsaw cooperative model on the social studies learning outcomes of eighth-grade students at SMP Negeri 2 Lubuk Sikaping.